Antifungal activity of phytotherapeutic preparation of Baccharis species from argentine Puna against clinically relevant fungi. (6th April 2020) - Carrizo, Silvana Lorena; Zampini, Iris Catiana; Sayago, Jorge Esteban; Simirgiotis, Mario Juan; Bórquez, Jorge; Cuello, Ana Soledad; Isla, María Inés
Abstract: Ethnopharmacological relevance: B. boliviensis and B. tola are used in traditional medicine in the Argentine Puna to treat skin and soft tissue infections and inflammatory processes in humans and animals. Aim of the study: To assess the potential of phytotherapeutic preparations of Baccharis species as antifungal agents against clinically relevant fungi and to determine the chemical composition of the extracts. Material and methods: Phytotherapeutic preparations of B. boliviensis and B. tola collected in Argentine Puna were evaluated as an antifungal agent against clinically relevant fungi (yeast, non-dermatophytes, and dermatophytes) isolated of patients from a local Hospital, and reference strains, using macrodilution and microdilution assays. The bioactivity was supported by UHPLC-OT-MS metabolome fingerprinting. Results: The results revealed that the plant preparations were active against most of evaluated fungal strains; B. boliviensis was more active than B. tola . Dermatophyte fungi strains were the most sensitive isolates. The phytotherapeutic preparation showed Minimal Inhibitory Concentration (MIC) values between 25 and 400 μg GAE/mL and Minimum Fungicidal Concentration (MFC) values between 50 and 400 μg GAE/mL. Regarding the phytochemical analysis, total phenolic and total flavonoid contents of hydroalcoholic preparation of B. boliviensis were greater than those of the B. tola extract. Both Baccharis species showed similar chromatographic patterns, fifty-two compounds were identified based on UHPLC-OT-MS including several terpenoids, flavonoids and phenolic acids that have been identified in this two endemic South American Baccharis species for the first time. Several identified compounds present antifungal properties, the presence of these compounds support the bioactivity of the Baccharis extracts. Conclusions: In this work the traditional use of both Baccharis species as an antimicrobial against commercial products resistant fungal strains was validate, principally against dermatophytes fungi such as T. rubrum, T. mentagrophytes, M. canis, and M. gypseum . These results indicate that the hydroalcoholic preparations could be used for the treatment of fungal infectious. Graphical abstract: Image 1